2017
DOI: 10.7567/jjap.56.08mb09
|View full text |Cite
|
Sign up to set email alerts
|

Improved opto-electronic properties of silicon heterojunction solar cells with SiOx/Tungsten-doped indium oxide double anti-reflective coatings

Abstract: Amorphous SiOx was prepared by plasma enhanced chemical vapor deposition (PECVD) to form SiOx/tungsten-doped indium oxide (IWO) double anti-reflective coatings for silicon heterojunction (SHJ) solar cell. The sheet resistance of SiOx/IWO stacks decreases due to plasma treatment during deposition process, which means thinner IWO film would be deposited for better optical response. However, the comparisons of three anti-reflective coating (ARC) structures reveal that SiOx film limits carier transport and the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…The ITO cells show better values for Rsh and c than the ZnO:Al samples probably due to the better conductivity and better contacts to both silver and n layer leading to a slightly better FF. Remarkable is the Rsh improve of the ZnO:Al sample after the SiO2 cap deposition which might be attributed to the TCO conductivity variation due to the hydrogen incorporation during the PECVD SiO2 deposition, as seen previously by Yu et al [10].…”
Section: C) Optical Benefits Of the Different Ar Approachessupporting
confidence: 71%
See 1 more Smart Citation
“…The ITO cells show better values for Rsh and c than the ZnO:Al samples probably due to the better conductivity and better contacts to both silver and n layer leading to a slightly better FF. Remarkable is the Rsh improve of the ZnO:Al sample after the SiO2 cap deposition which might be attributed to the TCO conductivity variation due to the hydrogen incorporation during the PECVD SiO2 deposition, as seen previously by Yu et al [10].…”
Section: C) Optical Benefits Of the Different Ar Approachessupporting
confidence: 71%
“…Supported by optical simulations, we demonstrate an optical improvement of the SHJ finished cells when introducing an additional plasma-enhanced chemical vapor deposited (PECVD) silicon dioxide (a-SiO2) antireflection (AR) layer on top of the ZnO:Al. This double AR stack concept has been used in the past by other groups using different materials (ITO, IWO as TCO and MgF2 or SiO2 as AR coating) showing also a clear optical improvement due to the double layer [8][9][10][11][12][13][14][15]. However, little or none of this AR benefit will remain in an encapsulated module due to the refractive index of the polymer encapsulation foil having the same value of about 1.5 as the a-SiO2.…”
Section: Introductionmentioning
confidence: 99%
“…These layers are among the doped indium oxide layers with the highest mobility 11 . Furthermore WO x doped InO x films (1 wt%) have been applied in silicon heterojunction solar cells as double anti reflective coating leading to up to 23 % efficiency 29 .…”
mentioning
confidence: 99%
“…In 2019, a number of groups demonstrated that SiN x /TCO composite layers at the front surface for rear-emitter SHJ solar cells can enhance the optical performance without damaging the lateral transport of carriers and the passivation. [93,97,98] In this architecture the parasitic absorption of the TCO can be reduced by designing a thinner TCO layer than the single-layer anti-reflective optimum (≈80 nm). In this case, a second anti-reflecting coating such as SiN has to be deposited on top of the TCO to minimize reflection losses.…”
Section: Reduction Of Parasitic Absorption In Tcomentioning
confidence: 99%